ZF and MMSE application for FBMC-QAM - Kamislioglu, Bircan; Akbal, Ayhan (Institute of Electrical and Electronics Engineers Inc., 2017)
In next generation communication systems high data rate, and higher transmission capacity through wireless channel are important for researchers. Filter bank based multicarrier (FBMC) modulation with offset quadrature amplitude modulation (OQAM) makes researchers interested due to its advantages over orthogonal frequency division multiplexing (OFDM). The paper indicates that OFDM, FBMC-QAM, multiple-input multiple output (MIMO) transmission layouts and channel estimation layouts study same logic. Also MIMO receiver design is realized for FBMC such as ZF, MMSE, ML techniques. Finally, FBMC-QAM and OFDM is compared about magnitude response, amplitude of subcarriers in frequency and BER performance and MIMO receiver techniques are compared about SER to SNR. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Demodulation; FBMC; Modulation; PSK; QAM